THE EXISTENCE OF LINGUISTIC IN THE ARTIFICIAL INTELLIGENCE (AI) ERA - Arkana Hady; Fadly Ramadhan Tanjung; Sholihatul Hamidah Daulay (Universitas Negeri Islam Sumatera Utara, 2024)
The emergence of AI change how people use technology. Most of the Artificial intelligence that integrated with technology are operated with language such as virtual assistants (alexa, siri, Google’s assistant) and NLP AI like ChatGPT chabot. Therefore, the role of linguistics fills that gap so the users could use them properly so it achieves it maximal potential. To fill this gap, the current research wants to examine that linguistics take a big role in AI era, the usage of AI cannot be separated with language. This research used literature review method by collecting and examining the related theories and studies regarding linguistics and AI, specifically virtual assistants and natural language processing (NLP). This research discovers that understanding linguistics, specifically phonology, morphology, and syntax can use AI in better ways and open it maximum potential.